Still spurious: A comment on attempts to revive cognitive ability tilts - Kimmo Sorjonen; Bo Melin; Gustav Nilsonne (PLoS ONE, 2025)
Ability tilts are within-individual differences between scores on two ability measures, e.g., math – verbal ability. We have shown in a series of reports that correlations between tilts and other variables are spurious consequences of associations to the constituent variables. Recently, Woodley of Menie et al. suggested that findings of incremental validity of tilts, over and above one of the constituent variables, refuted our claims of spuriousness. However, we show here that incremental validity of tilts are spurious consequences of incremental validity of the constituent variables. Moreover, Woodley of Menie et al. presented new results where so-called “tilt super-residuals” were attributable to shared environmental factors and they concluded that this finding confirmed a hypothesis that individuals specialize with respect to cognitive niches as an effort to adapt to stable environmental factors, alternatively do not specialize in the case of an unstable environment. However, we show that variance on “super-residualized” tilts attributable to shared environmental factors is a spurious consequence of adjusting for a variable (e.g., age) that is identical within twin couples. In summary, findings involving ability tilts still appear to be spurious.